ANALISIS KETERAMPILAN SERVIS ATAS BOLA VOLI PADA SISWA KELAS XI AGRIBISNIS TERNAK UNGGAS SMK NEGERI 1 BAWEN - Mulia Dharmika, Bagas; Ratimiasih, Yulia; Kusuma Prastiwi, Bertika (Journal of Physical Activity and Sports (JPAS), 2024)
This research aims to understand the potential of students of class XI Agribisnis Ternak Unggas SMK Negeri 1 Bawen in performing volleyball overhead serves because many students still have difficulties, such as shots that often fail to pass the net. This research applies a survey method with a quantitative method, and the assessment is carried out using an overhead serve skills rubric. All 64 students of class XI were made research participants. Information was reviewed explicitly and then presented in the form of a percentage. The results showed that most students were in the Good category (65.6%) with a score of 12–14, and the rest were in the Moderate category (34.4%) with a score of 9–11. No students achieved the Very Good, Less, or Very Less classification. The average student score was 11.97, included in the Moderate category. This finding indicates the need for learning improvements to help students improve their overhead service skills.